Analysis of MTNR1B gene polymorphisms in relationship with IRS2 gene variants, epicardial fat thickness, glucose homeostasis and cognitive performance in the elderly. (14th September 2017) - Mazzoccoli, Gianluigi; Dagostino, Mariangela Pia; Paroni, Giulia; Seripa, Davide; Ciccone, Filomena; Addante, Filomena; Favuzzi, Giovanni; Grandone, Elvira; Avola, Roberto; Mazza, Tommaso; Fusilli, Caterina; Greco, Antonio; et al.
ABSTARCT: Genome-wide association studies pinpointed common variants in or near the MTNR1B gene encoding MT2 melatonin receptor to be strongly associated with fasting glucose levels. IRS2 gene polymorphisms impact insulin resistance and epicardial fat (EF) thickness, which in turn is correlated with visceral adiposity, cognitive ability and risk for metabolic plus cardiovascular disease. We aimed to discover the interactions between MTNR1B and IRS2 gene polymorphisms, insulin sensitivity, EF thickness and cognitive performance in the elderly. In 60 subjects aged 60 years and older, we evaluated five single nucleotide polymorphisms (SNPs) within the MTNR1B locus (rs10830962, rs4753426, rs12804291, rs10830963, rs3781638), the Gly1057Asp variant of IRS2 gene (rs1805097), biochemical parameters, cognitive performance by the Mini Mental State Examination (MMSE) and EF thickness by transthoracic echocardiography. We found that MTNR1B and IRS2 gene variants impacted EF thickness, lipid profile and glucose homeostasis. IRS2 but not MTNR1B variants impacted MMSE scores. In conclusion, MTNR1B SNPs interact with IRS2 gene variant, correlate with the amount of epicardial adipose tissue and impact glucose homeostasis and lipid profile influencing cardiometabolic risk.